Higher Sensitivity and Earlier Identification of Celiac Disease Autoimmunity by a Nonradioactive Assay for Transglutaminase Autoantibodies. (26th December 2016) - Zhao, Zhiyuan; Miao, Dongmei; Waugh, Kathleen; Taki, Iman; Dong, Fran; Liu, Edwin; Rewers, Marian; Liu, Yu; Yu, Liping
Abstract : Higher sensitive transglutaminase autoantibody (TGA) assay will detect the onset of celiac disease (CD) autoimmunity earlier. In developing a nonradioactive assay for TGA, we utilized electrochemiluminescence (ECL) technology and compared it to a high-performance radioimmunoassay (RIA) currently being used to screen patients with type 1 diabetes (T1D) and genetically at-risk individuals for CD. We selected 183 T1D patients with 60 patients having received biopsy and analyzed 396 sequential samples from 73 young children longitudinally followed up with TGA seroconversion, with 27 undergoing biopsy. In addition, 112 age-matched healthy control subjects were included in the study. With the 99th percentile of specificity, the ECL assay detected significantly more TGA positivity among patients with T1D (133/183) than RIA (114/183) and more of the sequential samples (34%) from 73 children than RIA (18%). The TGA assay performed by ECL was positive in all 59 subjects with villous atrophy. Among 73 longitudinally followed up children, ECL assay had earlier detection of TGA on 34 children by a mean of 2.5 years. In conclusion, the new TGA assay by ECL has a higher sensitivity than the current RIA assay and may better predict the onset of CD.